Karakteristik Penyedap Rasa Alami dari Biji Bunga Matahari dan Kupang Putih dengan Hidrolisis Enzimatis - Wicaksono, Luqman A; Winarti, Sri (Universitas Pattimura, 2021)
Research has been carried out on the production of natural flavorings from sunflower seeds and white shells by an enzymatic process using endo- and exo-protease enzymes from papaya sap (papain) and biduri plant sap (calotropin). The study aimed to determine the effect of the concentration of the mixture of endo- and exo-protease enzymes and the incubation time on the characteristics and profiles of amino acids of natural flavoring from sunflower and white shells. A completely randomized design (CRD) which consisted of 2 factors, the enzyme concentration (0; 1.5; 3.0 and 4.5%) and the hydrolysis time (1, 2 and 3 hours)was applied in this research. The obtained data were subjected to analysis of variance. The Duncan multiple range test was used to see whether there were any significant differences between treatments. The results showed that the concentration of the mixture of endo- and exo-protease enzymes and incubation time significantly affected the degree of hydrolysis, dissolved protein, water content, Maillard product, water solubility index, oil absorption and yield. The best treatment in this study was the enzyme concentration of calotropin:papain 3% and 2 hours of incubation, resulting in flavoring with the characteristics: degree of hydrolysis of 96.81%; dissolved protein of 52.86%; Maillard products of 0.162%; water solubility index of 0.036; oil absorption of 1.88%; and the glutamic acid content of 78.678 mg/g. Keywords: Calotropin; flavorings; papain; sunflower seed; white shells ABSTRAK Telah dilakukan penelitian pembuatan penyedap rasa alami dari bahan baku biji bunga matahari dan kupang putih secara enzimatis menggunakan endo- dan ekso-enzim protease dari getah papaya (papain) dan getah tanaman biduri (calotropin). Tujuan penelitian adalah mengetahui pengaruh konsentrasi campuran endo- dan ekso-enzim protease, serta lama inkubasi terhadap karakteristik dan profil asam amino penyedap alami dari bunga matahari dan kupang putih. Rancangan penelitian adalah rancangan acak lengkap yang tersusun atas dua faktor, yaitu konsentrasi enzim (0; 1,5; 3,0 dan 4,5%) dan waktu hidrolisis (1, 2 dan 3 jam). Data yang diperoleh dianalisis menggunakan analisis keragaman, dan uji beda rataan menggunakan uji jarak berganda Duncan. Hasil penelitian menunjukkan bahwa konsentrasi campuran endo- dan ekso-enzim protease serta lama inkubasi berpengaruh nyata terhadap derajat hidrolisis, kadar protein terlarut, kadar air, produk maillard, indeks kelarutan air, daya serap minyak, dan rendemen penyedap rasa yang dihasilkan. Perlakuan terbaik pada penelitian ini adalah konsentrasi enzim calotropin:papain 3% dan lama inkubasi 2 jam, menghasilkan penyedap rasa dengan karakteristik: derajat hidrolisis 96,81%; kadar protein terlarut 52,86%; produk maillard 0,162%; indeks kelarutan air 0,036; daya serap minyak 1,88% dan kadar asam glutamat mencapai 78,678 mg/g. Kata kunci: Biji bunga matahari; calotropin; kupang putih; papain; penyedap rasa